Enhancing Kindergarten Teachers' Capacity: IT-Based Screening for Maladaptive Behavior During COVID-19 - Widyastuti Widyastuti; Ghozali Rusyid Affandi; Akbar Wiguna; Nurfi Laili (Universitas Muhammadiyah Sidoarjo, 2023)
In the context of the COVID-19 pandemic, the surge in maladaptive behavior among kindergarten students presents a pressing educational concern. Swift identification of such behaviors is crucial for effective intervention. This quantitative experimental study investigates the efficacy of the